KONSEP PELESTARIAN PUSAKA SAUJANA DI KAWASAN LEMBAH BADA - Mashuri, Mashuri (MEKTEK, 2011)
Bada Valley, one of the areas in Central Sulawesi, is rich with its natural dan cultural resources that need tobe developed and conserved. This article presents the concept of concervation that could be adapted in thisarea. The concept is called ecomuseum which implements the balace and the integrity of three elements;heritage, the participation from the community and the activity in the museum. It also gives priority toecologi activity to develop the area as the living museum. Through this concept, ecomuseum is expected togive contribution to increase the quality of live for the local community in Bada Valley